Magnetoconductance of graphene nanoribbons - Li, T.S.; Huang, Y.C.; Chang, S.C.; Chang, C.P.; Lin, M.F. (Philosophical magazine (Abingdon, England), 2009)
The electronic and transport properties of monolayer and AB-stacked bilayer zigzag graphene nanoribbons subject to the influences of a magnetic field are investigated theoretically. We demonstrate that the magnetic confinement and the size effect affect the electronic properties competitively. In the limit of a strong magnetic field, the magnetic length is much smaller than the ribbon width, and the bulk electrons are confined solely by the magnetic potential. Their properties are independent of the width, and the Landau levels appear. On the other hand, the size effect dominates in the case of narrow ribbons. In addition, the dispersion relations rely sensitively on the interlayer interactions. Such interactions will modify the subband curvature, create additional band-edge states, change the subband spacing or the energy gap, and separate the partial flat bands. The band structures are symmetric or asymmetric about the Fermi energy for monolayer or bilayer nanoribbons, respectively. The chemical-potential-dependent electrical and thermal conductance exhibits a stepwise increase behaviour. The competition between the magnetic confinement and the size effect will also be reflected in the transport properties. The features of the conductance are found to be strongly dependent on the field strength, number of layers, interlayer interactions, and temperature.